How to teach your children Shakespeare - Ludwig, Ken (New York : Broadway Books, 2013)
The author presents a way to instill an understanding and appreciation of Shakespeare's classic works in children, outlining a family-friendly method that incorporates the history of Shakespearean theater and society.
A midsummer night's dream -- Twelfth night -- Romeo and Juliet -- Interlude: Shakespeare's life and an overview of his work -- Macbeth -- Henry IV, part I -- As you like it -- Henry V -- Interlude: Hooray for Heminges and Condell -- Hamlet -- The tempest -- Epilogue: Appendix 1: A chronological list of Shakespeare's plays -- Appendix 2: Five additional longer passages -- Appendix 3: Fifty-five additional passages to teach your children if they want to continue -- Appendix 4: A list of favorite epigrams -- Appendix 5: Sample quotation pages.
Includes bibliographical references (pages 329-343).
Keywords: Shakespeare, William, -- 1564-1616 -- Study and teaching; Shakespeare, William, -- 1564-1616 -- Study and teaching (Elementary) -- Activity programs; Shakespeare, William, -- 1564-1616 -- Study and teaching (Middle school) -- Activity programs; Shakespeare, William, -- 1564-1616 -- Study and teaching (Secondary) -- Activity programs